A Physical Route to High Performance Heterojunction Composites: Experiments, Mechanism and Applications. Issue 6 (2016) - Li, Delong; Luo, Chengzhi; Pan, Chunxu
ABSTRACT: In order to enhance the photocatalytic efficiency of oxide semiconductors, variant processes have been proposed. The creation of the heterojunction composites has attracted considerable attentions and developed into an important research area for the high performance photocatalyst preparation. In this paper, we introduce the research progress on heterojunction composites which were prepared via a novel physical route with relatively high temperature treatments. It is hope that this mini-review can inspire research interest in the realm of heterojunction synthesis based on the thermal diffusion mechanism.